Pengaturan Klausul Pilihan Hukum dan Pilihan Forum dalam Perjanjian Asuransi Kapal di Indonesia - Firmansyah, Rahmadany; Sihabudin, Sihabudin; Sudirman, M. (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
The ship insurance agreement was prone to causing problems because the parties were in different jurisdictions, such as in the dispute over the PT. Purna Arthanugraha Insurance (PT. ASPAN) with PT. Indonesian Maritime Business Development (PT. Bumi Shipmanagement). The insurance policy agreement, in this case, was subject to and complied with English law, but the settlement of the case was filed in a court in Indonesia. This case became a legal problem in determining the choice of law arrangement and forum for resolving disputes. Based on these problems, this study aimed to analyze the regulation over the choice of law clause and the choice of forum in the ship insurance agreement. The approach used in this study was a case study approach and a statutory approach. The type of research used in this study was normative juridical, the data analysis technique used descriptive, interpretation, evaluation and argumentation techniques. The study results showed that the choice of law clause in the ship insurance agreement based on the agreement of the two parties referred to the applicable law in England, namely the Marine Insurance Act 1906. The setting of the forum choice clause in the ship insurance agreement was not regulated strictly and explicitly, so the dispute was submitted by one of the parties to the district court based on civil procedural law. Settlement of ship insurance agreement disputes through a lawsuit to the district court was not ideal because the district court's scope was limited to civil cases of a general nature.